Effects of Psidium guajava Leaf Infusion on Streptococci viridans - Hing Yi Chen; Ine Kuswardinah; Laili Aznur (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Dental caries is recognized as the most important oral burden. It is caused by the formation of lactate acid formed through reaction of bacteria and carbohydrates. Streptococci viridans has been proven as the primary etiologic agents for dental caries. Low accessibility in oral care services leads the Indonesian community to use plants in order to prevent dental caries. One of those plants is Psidium guajava (pink guava). The leaves were suggested to have antimicrobial effects on some gram-positive bacteria. When the organism is resistant to specific substance tested on media, a circular/inhibition zone around a disc containing antimicrobial substance was formed. The purpose of this study was to identify the presence of inhibition zones by infusion of Psidium guajava leaf on Streptococci viridians in vitro.Methods: This laboratory experiment was carried out in September to October 2014 at the Microbiology Laboratory, Faculty of Medicine, Universitas Padjadjaran. Infusions of Psidium guajava leaf were made into four different concentrations (10%, 25%, 50% and 100%, respectively) and the identification of inhibition zones on Streptococci viridans obtained from the laboratory was tested using modified disk diffusion test. Distilled water acted as negative control. The results were then interpreted after 24 hours of incubation. Every procedure was repeated three times.Results: All four concentrations of Psidium guajava leaf infusions have formed inhibition zones on the media, with the highest concentration (100%) producing largest average diameter.Conclusions: The infusion of Psidium guajava leaf produces inhibition zones on Streptococci virdans in vitro. [AMJ.2016;3(3):345–8] DOI: 10.15850/amj.v3n3.877